Bioreactor for mobilization of mesenchymal stem/stromal cells into scaffolds under mechanical stimulation: preliminary results - Gamez, Carolina; Schneider-Wald, Barbara Katharina; Schütte, Andy; Mack, Michael; Hauk, Luisa; Khan, Arif ul Maula; Gretz, Norbert; Stoffel, Marcus; Bieback, Karen; Schwarz, Markus (PLOS ONE, 2020)
Introduction: Articular cartilage (AC) is a viscoelastic tissue with a limited regenerative capability because of the lack of vasculature. Mechanical stimulation contributes to the homeostasis of functional AC since it promotes the delivery of nutrients, cytokines and growth factors between the distant chondrocytes. We hypothesized that biomechanical stimulation might enhance mobilization of endogenous mesenchymal stem/stromal cells (MSCs) from neighboring niches as the bone marrow. Aim: This study aimed to introduce a bioreactor for inducing mobilization of MSCs from one compartment to another above by mechanical stimulation in vitro. Methods: A novel mechanical system for evaluating mobilization of cells in a 3D context in vitro is presented. The system consists of a compression bioreactor able to induce loading on hydrogel-based scaffolds, custom-made software for settings management and data recording, and image based biological evaluation. Intermittent load was applied under a periodic regime with frequency of 0.3 Hz and unload phases of 10 seconds each 180 cycles over 24 hours. The mechanical stimulation acted on an alginate scaffold and a cell reservoir containing MSCs below it. The dynamic compression exerted amplitude of 200 μm as 10% strain regarding the original height of the scaffold. Results: The bioreactor was able to stimulate the scaffolds and the cells for 24.4 (±1.7) hours, exerting compression with vertical displacements of 185.8 (±17.8) μm and a force-amplitude of 1.87 (±1.37; min 0.31, max 4.42) N. Our results suggest that continuous mechanical stimulation hampered the viability of the cells located at the cell reservoir when comparing to intermittent mechanical stimulation (34.4 ± 2.0% vs. 66.8 ± 5.9%, respectively). Functionalizing alginate scaffolds with laminin-521 (LN521) seemed to enhance the mobilization of cells from 48 (±21) to 194 (±39) cells/mm3 after applying intermittent mechanical loading. Conclusion: The bioreactor presented here was able to provide mechanical stimulation that seemed to induce the mobilization of MSCs into LN521-alginate scaffolds under an intermittent loading regime.
Gesehen am 10.03.2020